Dynamic phenotypic heterogeneity and the evolution of multiple RNA subtypes in hepatocellular carcinoma: the PLANET study. Issue 3 (29th October 2021) - Zhai, Weiwei; Lai, Hannah; Kaya, Neslihan Arife; Chen, Jianbin; Yang, Hechuan; Lu, Bingxin; Lim, Jia Qi; Ma, Siming; Chew, Sin Chi; Chua, Khi Pin; Alvarez, Jacob Josiah Santiago; Chen, Pauline Jieqi; et al.
Abstract: Intra-tumor heterogeneity (ITH) is a key challenge in cancer treatment, but previous studies have focused mainly on the genomic alterations without exploring phenotypic (transcriptomic and immune) heterogeneity. Using one of the largest prospective surgical cohorts for hepatocellular carcinoma (HCC) with multi-region sampling, we sequenced whole genomes and paired transcriptomes from 67 HCC patients (331 samples). We found that while genomic ITH was rather constant across stages, phenotypic ITH had a very different trajectory and quickly diversified in stage II patients. Most strikingly, 30% of patients were found to contain more than one transcriptomic subtype within a single tumor. Such phenotypic ITH was found to be much more informative in predicting patient survival than genomic ITH and explains the poor efficacy of single-target systemic therapies in HCC. Taken together, we not only revealed an unprecedentedly dynamic landscape of phenotypic heterogeneity in HCC, but also highlighted the importance of studying phenotypic evolution across cancer types. Abstract : Using a prospective cohort for Hepatocellular Carcinoma (the PLANET study), this work revealed a dynamic landscape of phenotypic intra-tumor heterogeneity, providing several novel approaches for patient treatment and prognosis prediction.